(untitled) (Research Journal, 2023)
Home stay tourism has emerged as a promising avenue for income generation and community development in Nepal, particularly in rural areas where traditional forms of accommodation are scarce. This article explores the income generation opportunities offered by home stays in Ilam Municipality, Nepal, and delves into the impact of rural tourism on the local economy. The article also analyzes the challenges and opportunities associated with home stay development, emphasizing the importance of community-based tourism and its potential for economic growth, cultural preservation, and poverty alleviation. Drawing on qualitative approach, data were collected through the unstructured interview and direct interaction with local participants and visitors. The findings highlight the economic benefits of home stays, the empowerment of local communities, and the preservation of cultural heritage. However, challenges related to cultural authenticity, service quality, and equitable development are identified. The findings imply that the policymakers, tourism planners, and local communities should formulate effective plans and programs to enhance the sustainability and inclusivity of home stay tourism in Nepal.